An Integrated Learning Framework of Motivation, Pedagogy, and Resource Utilization: Implications for Student Achievement in Timor-Leste - Ridho, Muhammad Rasyid; Haifani, Maharani Fadhiyah; Araujo, Angelmo Alves de (Universitas Muhammadiyah Surakarta, 2026)
This study aims to examine the influence of learning motivation, instructional methods, and the utilization of learning resources on student learning achievement in State High Schools and Catholic High Schools in Ainaro, Timor-Leste. The research employed a quantitative non-experimental design with a correlational approach. The population consisted of 1,558 students, and a sample of 94 respondents was determined using the Taro Yamane formula. Data were collected through questionnaires, documentation, and observation, and analyzed using descriptive statistics and multiple linear regression with SPSS version 25. The results reveal that learning motivation, instructional methods, and learning resource utilization each have a significant partial effect on student learning achievement. Among these variables, the utilization of learning resources shows the strongest influence. Simultaneously, the three variables significantly affect learning achievement, with a coefficient of determination (R²) of 0.510, indicating that 51% of the variance in student performance is explained by the model. From a theoretical perspective, this study integrates the concepts of lifelong learning, innovative learning, and advanced learning, highlighting the importance of internal, pedagogical, and environmental factors in shaping educational outcomes. The findings suggest that improving student achievement requires a holistic approach that enhances motivation, promotes innovative teaching practices, and optimizes the use of learning resources.